Robert Capa the concerned photographer: analysis of the photograph The Falling Soldier and its localization - Susperregui Echeveste, Jose Manuel (Revista General de Información y Documentación, 2023)
The photograph The Falling Soldier is the paradigm for investigating the differences between reality and the ability of photography to represent it. In this article we take an exhaustive look at this image, which has been considered the best war photograph ever made and which, in turn, has generated controversy over its authenticity or staging. Despite the evidence demonstrated in various publications, both the International Center of Photography and the Magnum Agency have shown no interest in these contributions that have resolved the controversy. The silent attitude of the Magnum Agency is worrying because it is the advocate of the importance of photography in improving social justice and the general welfare of society. The attitude of the International Center of Photography is similar because when new evidence is published that tips the balance towards staging, they respond that further research is still needed. This article proves beyond doubt that The Falling Soldier was a staged photograph.